The European Union's Position in Global Foreign Direct Investment Flows and Stocks: Institutional Attempts to Improve It - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2021)
Global flows of foreign direct investment (FDI) have slowed down in recent years, which particularly affected developed countries, including those in the European Un- ion (EU). A general decrease in capital circulation in the form of FDI between the EU and the rest of the world has been observed. The aim of this paper is to assess the changes in the EU's position in global FDI flows and stocks and to discuss attempts made by EU institutions and the EU member states to improve this position. The EU can use the common investment policy to strengthen its investment position. The EU acquired the competence to conduct this policy based on the Lisbon Treaty, while its actual shape was determined in practice. Improving the EU's position in global FDI flows requires agreements regarding foreign investment, concluded at the EU level with other countries and integration groupings. Ensuring national treatment of investors before and after investing is important, as are solutions used for inves- tor protection, investor-state-dispute-settlements (ISDS), and the use of investment project screening to protect strategic sectors of the EU economy. The EU investment policy can mitigate the effects of slowing down FDI flows, create a more favorable climate for outgoing FDI, and protect vital interests for FDI coming into the EU from third countries.
Keywords: F2; F15; F21; 330; foreign direct investment (FDI); European Union; investment policy